Research on Capacity Configuration of Drilling Microgrid based on Gas-Energy Storage System - Xie, Xiaofeng; Ma, Haifeng; Wang, Guorong; Zhong, Lin; Shi, Xianfeng (International Journal of Electric Power and Energy Studies, 2026)
To address the industry challenges of mismatched power output from gas generators and dynamic downhole load demand in drilling operations, along with the lack of scientific configuration basis for the coordinated operation of energy storage systems and traditional power generation equipment, this study conducts an in-depth optimization study on a hybrid gas-energy storage power supply system using a 50DB drilling rig as the specific research object. Historical load power data of the rig during typical operating cycles were systematically collected and analyzed. Based on this, a cost optimization model for the coordinated gas-energy storage power supply was developed, aiming to minimize the total life-cycle cost. This model innovatively integrates key economic factors, including the initial investment and long-term operation and maintenance costs of the battery energy storage system, as well as the fuel consumption and maintenance costs of the gas generator sets. The optimization objectives are the lowest overall system cost and the optimal energy storage capacity configuration. The results indicate that: ① While meeting the actual power demand, the optimal capacity of the energy storage battery is 1870 kWh, and the optimal charging/discharging power is 992 kW; ② The number of gas generator sets on site can be optimized from the original 8 to 4. This allows the units to operate stably within their high-efficiency range, increasing the average operating efficiency significantly from a maximum of 22.7% before optimization to 42.6%; ③ Under extreme working conditions with the maximum load during drilling operations, the optimally configured energy storage system can independently support the full site load for 4 hours, greatly enhancing the reliability and resilience of the power supply system.